Profiles of local growth and industrial change: Facts and an explanation - Jens Suedekum; Wolfgang Dauth (European Regional Science Association (ERSA), 2013)
In this paper we take a detailed look at the sectoral anatomy of regional growth in German regions over the period 1978-2008. In the aggregate, the German economy is characterized by a secular decline of the manufacturing sector and a rise of the modern service economy. This trend of structural change (Petty?s law) by no means occurs uniformly across space, however. Some regions exhibit this trend even at an accelerated pace, while other regions develop their local economic structures against the trend and expand their manufacturing bases. We first develop a novel empirical approach that allows us to categorize all German regions into one out of three groups with ?pro-trend?, ?anti-trend? or ?featureless? regional growth. ?Pro-trend? regions exhibited a similar direction of industrial change like the nation as a whole, but at an accelerated speed. That is, booming industries tended to grow faster than in the national average while declining industries tended to disappear faster. Conversely, in ?anti-trend? regions industries grew that declined elsewhere, while national boom industries declined. In a second step, we then compare these different groups of regions from a descriptive point of view and report some interesting stylized facts about the initial characteristics and the subsequent growth performances of ?pro-trend? and ?anti-trend? regions. We show, for example, that the ?pro-trend? pattern tends to come with the best overall performance. Yet, this profile where regions forge ahead in developing a modern service economy was neither a guarantee nor a prerequisite for regional success. Many ?anti-trend? regions also had growth rates well above the national average. In other words, we observe strong differences in the sectoral anatomy of growth across regions that performed equally well overall. Finally, investigating the causes of these differential regional trends, we show that the exposure to international trade is an important reason of the divergent patterns of local industrial change.
Keywords: 330; Structural change; local industry compositions; trade exposure; local employment growth